The Oxford handbook of political ideologies - Freeden, Michael, 1944-; Sargent, Lyman Tower, 1940-; Stears, Marc, 1971- (Oxford handbooks, 2013)
This is the first comprehensive volume to offer a state of the art investigation both of the nature of political ideologies and of their main manifestations. The diversity of ideology studies is represented by a mixture of the range of theories that illuminate the field, combined with an appreciation of the changing complexity of concrete ideologies and the emergence of new ones. Ideologies, however, are always with us.The Handbook is divided into three sections: The first is divided into three sections: The first reflects some of the latest thinking about the development of ideology on an historical dimension, from the standpoints of conceptual history, Marx studies, social science theory and history, and leading schools of continental philosophy. The second includes some of the most recent interpretations and theories of ideology, all of which are sympathetic in their own ways to its exploration and close investigation, even when judiciously critical of its social impact. This section contains many of the more salient contemporary accounts of ideology. The third focuses on the leading ideological families and traditions, as well as on some of their cultural and geographical manifestations, incorporating both historical and contemporary perspectives.Each chapter is written by an expert in their field, bringing the latest approaches and understandings to their task. The Handbook will position the study of ideologies in the mainstream of political theory and political analysis and will attest to its indispensability both to courses on political theory and to scholars who wish to take their understanding of ideologies in new directions.